(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2021)
Starting from a judgement of the court of first instance of Milan about an international corruption case affair, the article highlights a disparity in sanctions for administrative corporate criminal liability, which is analyzed in the light of the adequacy of sanctions in connection with the principles of European Union law.